The Effect of Implementing the Make a Match Type Cooperative Learning Model on Interest in Learning Social Sciences in Class VII of SMP Negeri 3 Alu Keamatan Alu, POLMAN Regency, West Sulawesi - Darmawati A; Andi Tenri Ampa; Nur Afdhalia Usman (International Journal of Education, Vocational and Social Science, 2024)
This study aims to determine the effect and how much significance the effect of the make a match cooperative learning model has on the interest in learning Social Sciences for class VII students of SMP Negeri 3 Alu. This study uses a quantitative approach to the experimental method. The population is all class VII students of SMP Negeri 3 Alu, Alu District, totaling 216 students. The sample used for the study amounted to 72 consisting of 36 students in the control class and 36 other students in the experimental class. Data collection techniques using observation, questionnaires and documentation. Based on the results of hypothesis testing using the t-test and f-test analysis techniques, it shows that Fcount is 315.061 and the Ftable value is at a significance level of 5% with N = 36 of 4.130. From the results of this analysis it can be seen that Fcount is greater than ftable (315.061 > 4.130). So that Ho is rejected and Ha is accepted. Then obtained tcount = 17.750. ttable=2.032. So if you compare ttable and tcount then. tcount = 17.750> ttable = 2.032. then Ho is rejected and Ha is accepted. The determinant coefficient in the experimental class is 90.3%. While the coefficient of determinant in the control class is 58.3%. So the decision is that there is a significant influence between the make a match learning model on student learning interest.